2017
DOI: 10.1242/jcs.175943
|View full text |Cite
|
Sign up to set email alerts
|

Embryo–epithelium interactions during implantation at a glance

Abstract: At implantation, with the acquisition of a receptive phenotype in the uterine epithelium, an initial tenuous attachment of embryonic trophectoderm initiates reorganisation of epithelial polarity to enable stable embryo attachment and the differentiation of invasive trophoblasts. In this Cell Science at a Glance article, we describe cellular and molecular events during the epithelial phase of implantation in rodent, drawing on morphological studies both in vivo and in vitro, and genetic models. Evidence is emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
140
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(152 citation statements)
references
References 144 publications
4
140
0
4
Order By: Relevance
“…This is followed by the reduced expression of E‐cadherin by epithelial cells and loosening of cell–cell adhesion within the epithelial layer. The latter allows the infiltration of the trophoblast and commencement of implantation (Aplin & Ruane, 2017; Coutifaris et al, 1991; Kokkinos et al, 2010). The second line of research in humans has proposed that the binding protein L‐selectin is expressed by trophoblasts and interacts with its ligand on uterine epithelia (Feng et al, 2017; Fukuda & Sugihara, 2008; Genbacev et al, 2003; Lai et al, 2005).…”
Section: Adhesion Molecules and Reproductionmentioning
confidence: 99%
“…This is followed by the reduced expression of E‐cadherin by epithelial cells and loosening of cell–cell adhesion within the epithelial layer. The latter allows the infiltration of the trophoblast and commencement of implantation (Aplin & Ruane, 2017; Coutifaris et al, 1991; Kokkinos et al, 2010). The second line of research in humans has proposed that the binding protein L‐selectin is expressed by trophoblasts and interacts with its ligand on uterine epithelia (Feng et al, 2017; Fukuda & Sugihara, 2008; Genbacev et al, 2003; Lai et al, 2005).…”
Section: Adhesion Molecules and Reproductionmentioning
confidence: 99%
“…For successful implantation, however, gene expression in the endometrium in addition is regulated by the implanting blastocyst by precisely synchronized embryo-maternal interactions [60,61,62]. Both compartments of the endometrium are involved in this process: on the one hand, the epithelium has to allow adhesion of the embryo and invasion through the epithelium, on the other hand the stromal cells must be transformed to decidua cells which regulate trophoblast invasion and provide the placental blood supply necessary for embryo nutrition.…”
Section: Cell–cell Junctions During Implantation and Decidualizationmentioning
confidence: 99%
“…Degradation of the luminal epithelium and start of trophoblast invasion is observed from 5.5 dpc (mouse) or 6 dpc (rat) onwards [61,63]. Freeze fraction studies revealed that strands of tight junctions expand during the preimplantation phase of pregnancy on the lateral membrane of the uterine epithelial cells in pregnant rats [64] and in pseudopregnant rabbits [65].…”
Section: Cell–cell Junctions During Implantation and Decidualizationmentioning
confidence: 99%
“…To establish successful embryo implantation, a normal developmental blastocyst and a receptive endometrium are required, as well as a synchronized conversation at the maternal-fetal interface 2 . During an extremely limited period, which is called the “window of implantation”, uterine endometrium undergoes morphological, biochemical and genetic changes to transform into a receptive status which can accept the blastocyst 3 .…”
Section: Introductionmentioning
confidence: 99%